Urgensi Penetapan Kriteria Politik Uang dalam Peraturan Perundang-Undangan Atas Pelaksanaan Kampanye Menjelang Pemilihan Umum - Lira, Muhammad Adnan (Jurnal Delik ADPERTISI, 2024)
This study aims to examine the urgency of setting money political criteria in laws andregulations related to the implementation of campaigns ahead of the General Election inIndonesia. Democratic governments in Indonesia give participation rights to their citizens, butthe practice of money politics becomes a serious problem at various stages of elections. In thecontext of regulation, there are imperfections and weaknesses that make money politicspossible. Supervision by election agencies, such as the KPU and Bawaslu, also facedobstacles, particularly related to public participation in reporting violations. The politicalimpact of money includes the potential for the election of leaders who focus more on personalinterests than public interests. This research uses a normative approach with qualitativeanalysis of laws and regulations, literature, and legal theory. The results showed the need forimproved regulations, increased public awareness, and strengthened the role of electionsupervision institutions to prevent the practice of money politics. In conclusion, monetarysolutions through cooperation with the banking sector can help reduce the political impact ofmoney. This research contributes to developing strategies to prevent money politics to improvethe integrity of elections in Indonesia.